Exploring ADHD Symptoms and Associated Impairment across Development. Issue 6 (April 2022) - Niina, Ayako; Eyre, Olga; Wootton, Robyn; Stergiakouli, Evie; Thapar, Anita; Riglin, Lucy
Objective: ADHD symptoms typically decline with age, but less is known about whether the presentation of specific ADHD symptoms differs across development. This study aimed to examine the frequency and associated impairment of specific ADHD symptoms in childhood, adolescence, and young adulthood. Method: A prospective, longitudinal cohort, the Avon Longitudinal Study of Parents and Children, was utilized ( N  = 2, 327). ADHD symptoms and impairment were assessed using the Development and Well Being Assessment at ages 7, 15, and 25. Results: Specific ADHD symptom frequencies and their associated impairment varied across development for the majority of symptoms, although easily distracted was one of the most commonly reported symptoms at each age, and difficulty sustaining attention was consistently associated with high levels of impairment. Conclusion: These findings suggest differences in the presentations of ADHD symptoms across development: current understanding of how ADHD presents in childhood/adolescence may not be generalizable to young adulthood.